Novel Method for Sidelobe Level Suppression in Multielement Angled Dipole Array Antennas - Wang, Heesu; Byun, Gangil; Park, Yong Bae; Park, Ikmo (IEEE Access, 2022)
In this paper, we propose a one-dimensional (1D) array antenna with improved sidelobe level (SLL) and cross-polarization (x-pol) characteristics. The array elements constituting the 1D array antenna comprise different numbers of dipole elements, and each array element has a different gain and E-field phase. The positions of the array elements in the z-axis direction are adjusted to equalize their E-field phases in the far field, and the array elements are arranged symmetrically with respect to the z-axis to obtain a low x-pol. The same amount of power is supplied to all the array elements of the 1D array antenna of the proposed structure. Therefore, a complexly structured feeding network is not required to achieve a low SLL and low x-pol. The gain of the proposed array antenna with a corporate feeding network is 15.2 dBi, and its SLL and x-pol level are-21.3 dB and 20.3 dB, respectively. The-10 dB impedance bandwidth of the proposed array antenna is 35.6% (8.3-11.9 GHz).
Keywords: 1D arrays; Array elements; Array-antenna; Dipole arrays; Endfire antennas; Low sidelobe level; Millimeter-wave antennas; Printed dipole; Sidelobe levels; X bands; Dipole array; endfire antenna; low sidelobe level; millimeter-wave antenna; printed dipole; X-band